PERGESERAN REALISASI TINDAK KESANTUNAN DIREKTIF MEREDUKSI NILAI KESANTUNAN POSITIF DAN KARAKTER DI KALANGAN PESERTA DIDIK - Harun Djoko Prayitno; Abdul Ngalim; Norliza Jammaluddin (BAHASTRA, 2018)
Language politeness, especially politeness of directive actions among elementary school students is the main foundation for instilling the character building of children. This directive politeness action has decreased over time in line with the century of global communication and computing. This study aims to describe the shift in the realization of directive politeness act (DPA) among elementary students with a Javanese cultural background. This research method takes the form of qualitative with a dual case study strategy. Sources of research data include all elementary school students and teachers in Surakarta and Yogyakarta. Data collection techniques are carried out by observing techniques actively involved, observing free involvement, and reinforced by FGD techniques. The research data in the form of speech from DPA elementary school students in conducting language activities in a school environment both in formal and non-formal settings. Data analysis was carried out using Leech model of politeness scale technique which was strengthened by politeness analysis with the principle of social, cultural harmony, the harmony of the Gunarwan and Prayitno models. The results of the study abstract that: (a) the realization of the DPA students experience a shift in line with the shifting of the time and context of the wearer, (b) the realization of DPA can reduce the positive politeness values and psychological characteristics of the students' character, (c) the realization of the student's DPA This digital trend tends to use direct and literal methods in line with the influence of the context of communication patterns and centuries of practical computing, (d) the taxonomic shift in the dominant DPA in the sub-TKD requires, (e) the DPA taxonomy begs parallel with its realization in the sub-DPA pleading, (f) the taxonomic shift in DPA invites the dominant in the sub-DPA to persuade, (g) the taxonomic shift in DPA advises the dominant sub-DPA to remind, (h) the taxonomic shift in DPA reprimands the dominant sub-DPA satire, (i) the taxonomy of DPA prohibits parallel with the realization of the sub-DPA prohibits, (j) the character of the DPA used by elementary students with a Javanese cultural background shifts in line with shifting understanding the values of language politeness and understanding of character among the wearer.